Cooling liquid for crystal cutting and preparation method thereof

By preparing a coolant containing a specific proportion and type of components, the commercially available coolant has poor cooling effect, insufficient lubrication performance and poor defoaming effect when cutting crystals with high density and high hardness, and achieve higher processing quality and accuracy, reducing the risk of tool wear and crystal thermal damage.

CN119709305APending Publication Date: 2025-03-28FIRST MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411977460.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When cutting crystals with high density and high hardness, the commercially available coolant has poor cooling effect, insufficient lubrication performance, and poor defoaming effect, resulting in low processing quality and accuracy, and an increased risk of tool wear and crystal thermal damage.

Method used

A coolant is used, which consists of 42-48% base oil (diisopropyl adipate or neopentyl glycol dioleate), 6-10% extreme pressure agent (aminothiophosphate), 3.5-5.0% anti-rust agent (benzotriazole), 0.6-1.0% defoaming agent (polyether modified silicone oil), 2.4-2.8% surfactant (fat alcohol polyoxyethylene ether), 1.2-1.8% antioxidant (2,6-di-tert-butyl p-cresol) and 34-38% water, and is prepared by stirring and mixing.

Benefits of technology

The cooling effect, lubrication performance and defoaming effect of the coolant are improved, which significantly reduces the temperature of the processing area, reduces the risk of tool wear and crystal thermal damage, improves processing quality and accuracy, and at the same time extends the tool life and reduces cutting costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709305A_ABST
    Figure CN119709305A_ABST
Patent Text Reader

Abstract

The invention discloses a cooling liquid for crystal cutting and a preparation method thereof. The cooling liquid comprises the following components in parts by weight: 42-48 parts of base oil; 6-10 parts of an extreme pressure agent; 3.5 to 5.0 parts of an antirust agent; 0.6 to 1.0 part of a defoaming agent; 2.4 to 2.8 parts of a surfactant; 1.2 to 1.8 parts of an antioxidant; 34 to 40 parts of water; wherein the base oil is one or more of diisopropyl adipate and neopentyl glycol dioleate. The cooling liquid provided by the invention adopts diisopropyl adipate and / or neopentyl glycol dioleate as base oil, has a relatively good crystal cooling effect and good heat conduction performance, and can rapidly reduce the temperature of a processing area and reduce the wear of a cutter and the thermal damage of the crystal. According to the cooling liquid disclosed by the invention, the base oil is combined with all the components, so that the lubricating property of the cooling liquid is relatively strong, the cutting force and the friction force are reduced, and the crystal processing quality and efficiency are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coolants, and in particular relates to a coolant for crystal cutting and a preparation method thereof. Background Art

[0002] Crystals generally need to be processed into standard-sized wafers through a cutting process. As the market's requirements for wafer quality become higher and higher, higher requirements are placed on the crystal cutting process. Coolant has a great impact on the processing quality and processing accuracy of the crystal cutting process. Improving the comprehensive performance of the coolant plays a vital role in improving the quality of the wafer.

[0003] The coolants currently available on the market can basically meet the cutting requirements for ordinary crystals, but for some crystals with high density and high hardness (such as scintillating crystals), the coolants available on the market have defects such as poor cooling effect, insufficient lubrication performance, and poor defoaming effect. The cooling effect is poor, and the temperature in the processing area cannot be quickly reduced, which increases the risk of tool wear and the crystal is susceptible to thermal damage. The lubrication performance is insufficient, and it is difficult to form a stable and good lubrication film, which affects the processing quality and efficiency. The defoaming effect is poor, and the presence of foam reduces the stability of the coolant, interferes with the cutting process, and affects the cutting accuracy. Therefore, it is very necessary to develop a coolant with good cooling effect, superior lubrication performance, and good defoaming effect for crystals with high density and high hardness. Summary of the invention

[0004] The purpose of the present invention is to provide a cooling liquid for crystal cutting with good cooling performance, good lubrication effect and good defoaming effect and a preparation method thereof.

[0005] In a first aspect, the present invention provides a cooling liquid for crystal cutting and a preparation method thereof, which adopts the following technical scheme: A cooling liquid for crystal cutting, comprising the following components in parts by weight: 42~48 parts of base oil; 6~10 parts of extreme pressure agent; 3.5~5.0 parts of rust inhibitor; 0.6~1.0 parts of defoaming agent; 2.4~2.8 parts of surfactant; 1.2~1.8 parts of antioxidant; 34~38 parts of water; Wherein: the base oil is one or two of diisopropyl adipate and neopentyl glycol dioleate.

[0006] Preferably, the coolant for crystal cutting comprises the following components in parts by weight: 45-47 parts of base oil; 7-9 parts of extreme pressure agent; 4-4.5 parts of rust inhibitor; 0.8-1.0 parts of defoaming agent; 2.4-2.6 parts of surfactant; 1.4-1.6 parts of antioxidant; 35-37 parts of water.

[0007] Further preferably, the coolant for crystal cutting comprises the following components in weight proportion: 46 parts of base oil; 8 parts of extreme pressure agent; 4.5 parts of rust inhibitor; 0.8 parts of defoaming agent; 2.6 parts of surfactant; 1.6 parts of antioxidant; and 36.5 parts of water.

[0008] Preferably, the extreme pressure agent is one or more of thiophosphate amine salt (T307), thiophosphate secondary alcohol zinc salt (T205), and dialkyl dithiophosphate zinc; more preferably, thiophosphate amine salt.

[0009] Preferably, the rust inhibitor is one or more of petroleum sulfonate, dodecenylsuccinic acid and benzotriazole; more preferably benzotriazole.

[0010] Preferably, the surfactant is one or more of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, and sorbitan fatty acid ester polyoxyethylene ether; more preferably, fatty alcohol polyoxyethylene ether.

[0011] Preferably, the defoaming agent is one or more of polyether-modified silicone oil, alkyl-modified silicone oil, and fluorine-modified silicone oil; more preferably, it is polyether-modified silicone oil.

[0012] Preferably, the antioxidant is one or more of 2,6-di-tert-butyl-p-cresol, 4,4'-methylenebis(2,6-di-tert-butylphenol), 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid octadecyl; more preferably 2,6-di-tert-butyl-p-cresol.

[0013] Preferably, the crystal is a scintillation crystal, and more preferably a LYSO scintillation crystal.

[0014] In a second aspect, the present invention provides a method for preparing a coolant for crystal cutting, comprising the following steps: The base oil, extreme pressure agent, rust inhibitor, defoamer, surfactant and antioxidant are mixed, and then water is added and stirred to obtain the product.

[0015] Preferably, the stirring time is 10 to 15 minutes.

[0016] The above one or more technical solutions of the present invention can achieve at least one of the following beneficial effects: (1) The coolant of the present invention uses diisopropyl adipate and / or neopentyl glycol dioleate as the base oil, which has a good cooling effect on the crystal and good thermal conductivity, can quickly reduce the temperature of the processing area, reduce the wear of the cutting machine tool and the thermal damage to the crystal.

[0017] (2) The base oil in the coolant of the present invention is combined with various components to make the coolant have stronger lubricity and form a good lubricating film, thereby reducing cutting force and friction and improving crystal processing quality and efficiency.

[0018] (3) The defoaming agent in the coolant of the present invention has high compatibility with the various components and can effectively reduce the generation of foam, thereby improving the stability and reliability of the coolant and improving the processing accuracy of the crystal.

[0019] (4) The present invention adjusts the ratio of each component in the coolant so that the coolant has good cooling effect, lubrication effect, rust prevention effect and cleaning effect, thereby effectively improving the cutting quality and cutting accuracy of the crystal. In addition, the use of the coolant of the present invention can extend the life of the cutting machine tool, reduce the frequency of coolant replacement, and significantly reduce the cutting cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A picture of the circulating water tank when cutting LYSO crystals using the coolant in Example 1 for Application Example 1.

[0021] Figure 2 Photo of the circulating water tank used to cut LYSO crystals using commercially available coolant in Application Example 1. DETAILED DESCRIPTION

[0022] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments. Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0023] In the present invention, the polyether-modified silicone oil is dy-et333 polyether-modified silicone oil from Shandong Dayi Chemical Co., Ltd.; the alkyl-modified silicone oil is jp-108 long-chain alkylphenyl-modified silicone oil from Shenzhen Jipeng Industrial Co., Ltd.; the fluorine-modified silicone oil is PB95924 hydroxyl fluorosilicone oil from Guangdong Wengjiang Chemical Reagent Co., Ltd. The commercially available coolant is trim model coolant from Master Chemical Company.

[0024] Example 1 The composition of the coolant in this embodiment is: 46 parts of diisopropyl adipate, 8 parts of thiophosphate amine salt (T307), 4.5 parts of benzotriazole, 0.8 parts of polyether modified silicone oil, 2.6 parts of fatty alcohol polyoxyethylene ether, 1.6 parts of 2,6-di-tert-butyl-p-cresol, and 36.5 parts of water.

[0025] Diisopropyl adipate, thiophosphate amine salt, benzotriazole, polyether modified silicone oil, fatty alcohol polyoxyethylene ether and 2,6-di-tert-butyl-p-cresol are mixed, water is added, and the mixture is stirred for 15 minutes to obtain a coolant.

[0026] Comparative Example 1 This comparative example includes multiple groups of coolants, and the specific composition of the coolants can be seen in Table 1.

[0027] Table 1 The numbers in the table are in parts by mass.

[0028] Example 2 This embodiment includes multiple groups of coolants. The specific composition of the coolants can be seen in Table 2. The preparation method is the same as that of Example 1.

[0029] Table 2 The cooling performance, lubrication performance and stability of the coolants of the formulas 1 to 3 in Example 1, Comparative Example 1 and the formulas 4 to 8 in Example 2 were tested. The specific test methods are as follows: (1) Cooling performance test: Each group of coolant samples was placed in a constant temperature water bath, the initial temperature was set to 50°C, and then a heating rod was used to simulate the processing heat source. The center of the coolant sample was heated to 90°C and then stopped heating. The time required for the coolant to cool naturally from 90°C to 60°C was recorded. The experimental results are shown in Table 3 below (unit: min).

[0030] Table 3 (2) Lubrication performance test: Using a four-ball friction tester, the friction coefficient between the steel balls was measured under a certain load (200N) and rotation speed (1200rpm). Each group of coolant samples was tested three times and the average value was taken. The results are shown in Table 4 below.

[0031] Table 4 (3) Stability observation: Place each group of coolant samples in a transparent glass container and leave it for 72 hours to observe whether there is any stratification. The results can be seen in Table 5.

[0032] Table 5 Combined with the test data in Tables 3 to 5, the changes in the proportion and type of base oil in the coolant have a certain influence on the cooling effect, lubrication performance and stability performance of the coolant. On the whole, the comprehensive performance of the coolant in Example 1 is the best, but the coolants of formulas 4 to 8 in Example 2 also have good cooling effect, lubrication performance and stability performance; but the coolants of formulas 1 to 3 in Comparative Example 1 have very poor stability performance, which is easy to affect the cutting accuracy during actual use.

[0033] Example 3 This embodiment includes multiple groups of coolants, and the specific composition of the coolants can be seen in Table 6; the preparation method is the same as that of Example 1.

[0034] Table 6 The coolants of Example 1 and formulations 9 to 16 in this example were subjected to tool wear simulation tests and high temperature and high pressure stability tests; the specific test methods and test data are as follows: (1) Tool wear simulation test: A tool wear simulation device was used to make a high-speed steel tool slide relative to a carbon steel workpiece under a certain pressure (500N). At the same time, a coolant sample was sprayed into the contact area between the tool and the workpiece at a flow rate of 5mL / s to simulate the cutting process. After each group of samples was tested for 1 hour, the wear width of the tool back face was measured using an optical microscope. The test results are shown in Table 7.

[0035] Table 7 (2) High temperature and high pressure stability test: Each group of coolant samples was placed in a high pressure reactor and maintained at 150°C and 2MPa for 4 hours. The viscosity change rate of the coolant (measured by a rotational viscometer) and the content of extreme pressure agent decomposition products (using chemical analysis methods) were then tested. The smaller the viscosity change rate and the lower the content of extreme pressure agent decomposition products, the better the stability. The test results are shown in Table 8.

[0036] Table 8 According to the tool wear simulation test and high temperature and high pressure stability test results in Tables 7 and 8, changes in the type and proportion of extreme pressure agents in the coolant have a certain impact on tool wear performance and high temperature and high pressure stability. Overall, the coolant of Example 1 has the best comprehensive performance, and the coolants of formulations 9 to 16 also have good tool wear and high temperature and high pressure stability.

[0037] Example 4 This embodiment includes multiple groups of coolants, and the specific composition of the coolants can be seen in Table 9; the preparation method is the same as that of Example 1.

[0038] Table 9 The coolants of Example 1 and formulations 17 to 24 in this example were subjected to a salt spray test: a carbon steel test piece (size 50 mm×50 mm×2 mm) after being immersed in the coolant for 1 hour was placed in a salt spray test chamber and subjected to a salt spray test according to standard ASTM B117, with a spray solution of 5% NaCl solution, a temperature set at 35°C, a spray pressure of 120 KPa, and a spray volume of 2 mL / 80 cm² / h. The time when rust spots began to appear on the test piece was recorded, and the results are shown in Table 10 below.

[0039] Table 10 According to the test results of the salt spray test in Table 10, it can be seen that the change in the type and proportion of the rust inhibitor in the coolant has a certain influence on the rust prevention effect. Overall, the coolant of Example 1 has the best rust prevention effect; the coolants of formulas 17 to 24 also have good rust prevention effects.

[0040] Example 5 This embodiment includes multiple groups of coolants, and the specific composition of the coolants can be seen in Table 11; the preparation method is the same as that of Example 1.

[0041] Table 11 The cleaning performance of the coolants of Example 1 and formulations 25 to 32 in this example was tested, and the specific test method and test results are as follows.

[0042] Cleaning performance test: A glass sheet with simulated dirt (mixed with mineral oil, metal powder and cutting fluid additives) was prepared and immersed in a coolant sample at 40°C for 30 minutes, then cleaned in an ultrasonic cleaner for 10 minutes, and finally the cleaning performance was evaluated by measuring the amount of residual dirt on the surface of the glass sheet (using the weighing method to measure the weight difference of the glass sheet before and after cleaning). The results are shown in Table 12 below.

[0043] Table 12 According to the test results of the cleaning performance in Table 12, the change of the type and proportion of the surfactant in the coolant has a certain effect on the cleaning performance. Overall, the coolant of Example 1 has the best cleaning effect; the coolants of formulations 25 to 32 also have good cleaning effects.

[0044] Example 6 This embodiment includes multiple groups of coolants, and the specific components of the coolants can be seen in Table 13; the preparation method is the same as that of Example 1. Table 13 The anti-oxidation performance test was conducted on the coolant of Example 1 and the coolants of formulations 33 to 40 in this example. The specific test method and test results are as follows.

[0045] Accelerated oxidation test: Each group of coolant samples was placed in a constant temperature oxidation chamber, oxidized for 72 hours at 80°C and an oxygen flow rate of 50 mL / min, and then the acid value change (using acid-base titration method) and viscosity change rate (measured using a rotational viscometer) of the coolant were measured. The smaller the acid value change and the smaller the viscosity change rate, the better the antioxidant performance. The results are shown in Table 14 below.

[0046] Table 14 According to the accelerated oxidation test results in Table 14, it can be seen that the changes in the type and proportion of antioxidants in the coolant have a certain effect on the antioxidant performance. Overall, the coolant of Example 1 has the best antioxidant effect, and the coolants of formulations 25 to 32 also have good antioxidant effects.

[0047] Example 7 This embodiment includes multiple groups of coolants, and the specific components of the coolants can be seen in Table 15; the preparation method is the same as that of Example 1.

[0048] Table 15 A preliminary foam observation experiment was conducted on the coolant of Example 1 and the coolants of formulas 41 to 51. The specific experimental method is as follows: each group of coolant samples was placed in a stirrer, stirred at a speed of 800r / min for 5min, and then the stirring was stopped to observe the amount of foam generated and the defoaming speed (qualitative evaluation by naked eye). The test results show that the coolant in Example 1 exhibits good defoaming performance, less foam generation and faster defoaming speed; the coolant in formula 45 has good defoaming performance, but the overall effect is not as good as that of Example 1; the defoaming effect of the coolant in formula 46 is acceptable, but the overall effect is not as good as that of Example 1; the coolant in formulas 49 to 51 uses acetylene glycol as a defoaming agent, and its defoaming performance is somewhat reduced compared with the coolants in Example 1 and formulas 41 to 48.

[0049] Example 8 This embodiment includes multiple groups of coolants, and the specific composition of the coolants can be seen in Table 16; the preparation method is the same as that of Example 1.

[0050] Table 16 The coolants of formulas 52 to 55 were subjected to foam generation speed test, foam quantity test and defoaming time test. The specific test methods and test results are as follows.

[0051] (1) Foam generation speed test: The coolant is placed in a foam generation device, through which compressed air is introduced into the coolant at a constant flow rate (50 mL / min) to simulate the stirring and gas mixing during the crystal cutting process, thereby generating foam. Within 0 to 5 minutes after the start of ventilation, the height of the foam in each group of coolant samples is recorded every 1 minute (measured using a ruler with an accuracy of 1 mm). The measurement results show that the foam generation speed of the coolant in formula 52 is the slowest, with a foam height of only 15 mm at 5 minutes; the foam height of the coolant in formula 52 reaches 25 mm; the foam height of the coolant in formula 54 is 22 mm; and the foam height of the coolant in formula 55 is the highest, reaching 35 mm. It can be seen that based on the composition of the coolant of the present invention, polyether-modified silicone oil is significantly better than other defoamers in inhibiting foam generation.

[0052] (2) Foam quantity test: The coolant is placed in a foam generating device, through which compressed air is introduced into the coolant at a constant flow rate (50 mL / min) to simulate the stirring and gas mixing during the crystal cutting process. The air is ventilated for 5 minutes, and the ventilation is immediately stopped. Wait for 1 minute for the foam to stabilize, and then the foam in each group of coolant samples is collected using a graduated cylinder. The measurement results show that the total amount of foam generated by the coolant of formula 52 is 150 mL, the amount of foam generated by the coolant of formula 53 is 220 mL, the amount of foam generated by the coolant of formula 54 is 200 mL, and the amount of foam generated by the coolant of formula 55 is the largest, reaching 300 mL. This shows that based on the composition of the coolant of the present invention, polyether-modified silicone oil has an advantage in reducing the amount of foam generated.

[0053] Application Example 1 The coolant of Example 1 and the commercially available coolant were used to carry out an actual LYSO scintillation crystal cutting experiment. The cutting was carried out using an internal circle cutting machine with the following processing parameters: cutting speed 50 mm / min, feed rate 0.05 mm / revolution, and cutting depth 2 mm.

[0054] Processing area temperature measurement: A thermal imager was used to monitor the processing area temperature in real time. During the processing, the average temperature of the processing area was 120°C when a commercially available coolant was used; when the coolant in Example 1 was used, the average temperature of the processing area was stabilized at around 75°C, indicating that the use of the coolant in Example 1 can effectively reduce the processing area temperature and reduce the risk of thermal damage to the crystal.

[0055] Tool wear measurement: After cutting 100 LYSO scintillating crystals, the tool back surface wear width was measured using an optical microscope. When commercially available coolant was used, the tool wear width was 0.5 mm on average; when the coolant in Example 1 was used, the tool wear width was 0.18 mm on average, indicating that the use of the coolant in Example 1 can reduce tool wear.

[0056] Processing accuracy measurement: The dimensional accuracy of the cut crystals was measured using a three-dimensional coordinate measuring machine. When commercially available coolants were used, the proportion of crystal size deviation within the range of ±0.05 mm was 80%; when the coolant in Example 1 was used, the proportion increased to 96%, indicating that the use of the coolant in Example 1 can improve the processing accuracy.

[0057] Coolant stability observation: The entire processing process was observed for 5 hours to observe the foam generation and stability of the coolant. The foam of the coolant in Example 1 can be seen Figure 1 The amount of foam produced is very small, and the coolant remains stable without stratification or deterioration. The foam of commercially available coolants can be seen Figure 2 , it has a large amount of foam and no stratification.

[0058] Observation of cleaning effect: The surface impurities of the cut crystals were observed using a scanning electron microscope. When the commercially available coolant was used, there were obvious impurities such as metal chips and oil stains on the surface of the crystals. After using the coolant in Example 1, the impurities on the surface of the crystals were significantly reduced, and the cleanliness was higher.

[0059] Application Example 2 The coolant of Example 1 was applied to a lithium tantalate crystal cutting experiment. An internal cutting machine was used for cutting. The processing parameters were: cutting speed 50 mm / min, feed rate 0.05 mm / revolution, and cutting depth 2 mm.

[0060] Temperature measurement of processing area: A thermal imager is used to monitor the temperature of the processing area in real time. During the processing, the average temperature of the lithium tantalate crystal processing area is about 90°C.

[0061] Tool wear measurement: After cutting 100 lithium tantalate crystals, the tool wear width was measured using an optical microscope. After cutting lithium tantalate crystals, the tool wear width was an average of 0.30 mm.

[0062] Processing accuracy measurement: Use a three-coordinate measuring machine to measure the size accuracy of the cut crystal; the proportion of lithium tantalate crystal size deviation within the range of ±0.05 mm is 85%.

[0063] Coolant stability observation: Observe the foam generation and stability of the coolant for 5 hours during the entire processing process. When processing lithium tantalate crystals, the amount of foam is acceptable (the foam is slightly increased compared to processing LYSO scintillating crystals), and the coolant is slightly turbid.

[0064] Observation of cleaning effect: The surface impurities of the cut crystals were observed using a scanning electron microscope. After processing, a small amount of metal chips, oil stains and other impurities remained in the lithium tantalate crystals; the overall cleanliness was not as good as that of the processed LYSO scintillation crystals.

[0065] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A cooling liquid for crystal cutting, characterized in that: According to the weight ratio, it includes the following components: 42~48 parts of base oil; 6~10 parts of extreme pressure agent; 3.5~5.0 parts of rust inhibitor; 0.6~1.0 parts of defoaming agent; 2.4~2.8 parts of surfactant; 1.2~1.8 parts of antioxidant; 34~40 parts of water; Wherein: the base oil is one or two of diisopropyl adipate and neopentyl glycol dioleate.

2. The coolant for crystal cutting according to claim 1, characterized in that: According to the weight ratio, it includes the following components: 45~47 parts of base oil; 7~9 parts of extreme pressure agent; 4~4.5 parts of rust inhibitor; 0.8~1.0 parts of defoaming agent; 2.4~2.6 parts of surfactant; 1.4~1.6 parts of antioxidant; 35~37 parts of water.

3. The coolant for crystal cutting according to claim 1, characterized in that: According to the weight ratio, it includes the following components: 46 parts of base oil; 8 parts of extreme pressure agent; 4.5 parts of rust inhibitor; 0.8 parts of defoaming agent; 2.6 parts of surfactant; 1.6 parts of antioxidant; 36.5 parts of water.

4. The coolant for crystal cutting according to any one of claims 1 to 3, characterized in that: The extreme pressure agent is one or more of thiophosphate amine salt, thiophosphate secondary alcohol zinc salt, and dialkyl dithiophosphate zinc.

5. The coolant for crystal cutting according to any one of claims 1 to 3, characterized in that: The rust inhibitor is one or more of petroleum sulfonate, dodecenylsuccinic acid and benzotriazole.

6. The coolant for crystal cutting according to any one of claims 1 to 3, characterized in that: The surfactant is one or more of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, and sorbitan fatty acid ester polyoxyethylene ether.

7. The coolant for crystal cutting according to any one of claims 1 to 3, characterized in that: The defoaming agent is one or more of polyether modified silicone oil, alkyl modified silicone oil and fluorine modified silicone oil.

8. The coolant for crystal cutting according to any one of claims 1 to 3, characterized in that: The antioxidant is one or more of 2,6-di-tert-butyl-p-cresol, 4,4'-methylenebis(2,6-di-tert-butylphenol), and 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid octadecyl ester.

9. The coolant for crystal cutting according to any one of claims 1 to 3, characterized in that: The crystal is a scintillation crystal.

10. A method for preparing a coolant for crystal cutting according to any one of claims 1 to 9, characterized in that: The following steps are involved: The base oil, extreme pressure agent, rust inhibitor, defoamer, surfactant and antioxidant are mixed, and then water is added and stirred to obtain the product.